What Influences People’s Tradeoff Decisions Between CO2 Emissions and Travel Time? An Experiment With Anchors and Normative Messages - Andersson, Hanna; Ahonen-Jonnarth, Ulla; Holmgren, Mattias; Marsh, John E.; Wallhagen, Marita; Bökman, Fredrik (Frontiers in Psychology, 2021)
One of today’s great challenges is to adjust our behavior so that we can avoid a major climate disaster. To do so, we must make sacrifices for the sake of the environment. The study reported here investigated how anchors (extrinsic motivational-free information) and normative messages (extrinsic motivational information) affect people’s tradeoffs between travel time and carbon dioxide (CO2) emission in the context of car travel and if any interactions with environmental concern (an intrinsic motivational factor) are observable. In this study, people received either a CO2, health or no normative message with either a high or low anchor. People that received both a high anchor and a CO2 emission normative message were willing to travel for a longer time than those that only received a high anchor. If a low anchor was presented, no differences in willingness to travel for a longer time were found between the three different conditions of normative messages groups, i.e., CO2 normative message, health normative message, or no normative message. People with higher concern for the environment were found to be willing to travel for a longer time than those with lower concern for the environment. Further, people with higher concern for the environment were willing to travel for a longer time when a high anchor was presented. These results suggest that anchors and normative messages are among the many factors that can influence people’s tradeoffs between CO2 emission and travel time, and that various factors may have to be combined to increase their influence towards pro-environmental behavior and decisions.